4D imaging of the volcano feeding system beneath the urban area of the Campi Flegrei caldera - Tizzani, Pietro; Fernández, José; Vitale, Andrea; Escayo, Joaquín; Barone, Andrea; Castaldo, Raffaele; Pepe, Susi; De Novellis, Vincenzo; Solaro, Giuseppe; Pepe, Antonio; Tramelli, Anna; Hu, Zhongbo; et al. (Remote sensing of environment, 2024)
This paper describes an approach to analyze ground deformation data collected by InSAR (Interferometric Synthetic Aperture Radar) imaging the volcano feeding system (VFS) beneath a caldera. The approach is applied to the Campi Flegrei caldera in southern Italy, a densely populated area at high risk for volcanic eruption. The method is a 4D tomographic inversion that considers a combination of 3D pressure sources and dislocations (strike-slip, dip-slip and tensile) acting simultaneously. This is in contrast to traditional methods that assume a priori geometries and type for the volcanic source. Another novelty is that we carry out a time-series analysis of multifrequency InSAR displacement data. The analysis of these multiplatform and multifrequency InSAR data from 2011 to 2022 reveals an inflating source at a depth of 3–4 km that is interpreted as a pressurized magmatic intrusion. The source broadens and migrates laterally over time, with a possible new magmatic pulse arriving in 2018–2020. The model also identifies a shallow region (at 400 m depth) that may be feeding fumaroles in the area. The analysis also reveals a zone of weakness (dip-slip) that could influence the path of rising magma. This method provides a more detailed dynamic 4 - dimensional image of the VFS than previously possible and could be used to improve hazard assessments in active volcanic areas. •InSAR and state-of-the-art inversion technique to improve volcano monitoring.•Ground deformation of Campi Flegrei caldera from 2011 to 2022.•4D geodetic tomography of the volcano feeding system below the caldera.•Identification of magmatic fluids paths and fractured regions below the caldera.